Integrating Learning Management System and Clasification Learning Media Based On Two Dimension Animation - Suarya Putra, I Nyoman Agus; Sustiawati, Ni Luh; Udayana, Anak Agung Gde Bagus; Suardana, I Wayan (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2024)
This research aims to combine the advantages of LMS technology with the potential of two-dimensional animated learning media in an educational context. This research explores the basic concept of a Learning Management System (LMS) and its advantages in providing a structured platform for delivering learning material, student-teacher interaction, and evaluating learning progress. LMS offers broad accessibility, student progress tracking, and the ability to facilitate collaborative learning. The research focus shifted to the potential of two-dimensional animation-based classification learning media. Two-dimensional animation offers interesting and engaging visualizations and can help students understand complex concepts better. In this context, this research integrates the visual power of animation with the learning structure provided by the LMS. This integration is expected to increase student engagement, facilitate a deeper understanding of concepts, and increase information retention. In addition, this combination is also expected to improve the overall quality of teaching by enabling the use of more innovative and interactive teaching methods. This research aims to contribute to our understanding of how learning technology can be integrated effectively to improve student's learning experiences. Thus, it is hoped that the results of this research can provide valuable insight into the development of better learning practices.